VAVILOV INSTITUTE CABBAGE COLLECTION: STAGES OF FORMATION AND RESEARCH - A. M. Artemyeva; Yu. V. Chesnokov (Вавиловский журнал генетики и селекции)
Key stages of the formation and research of the world cabbage collection kept at the Vavilov Research Institute of Plant Industry (VIR) are outlined. The conceptual development of ecogeographical, biochemical, immunological, and molecular investigation of cabbage accessions is shown by the example of Brassica rapa L. Major results of the organization and research of core collections of Brassica species, addition of new accessions to the collection, raise and characterization of initial breeding material and systemic organization of cabbage accessions inside the world collection by means of both conventional and new methods of investigation and evaluation including QTL analysis and association mapping are presented.